THE IMPACT OF 3R TRAINING IN BASIC EDUCATION TOWARD WASTE MANAGEMENT IN PALANGKA RAYA CITY - Akhmad Syarif (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
The reason why this research was held is because of the complexity of waste problem in big city has been spreading to Palangka Raya city. Lack of people awareness about waste and the waste management also assuming that waste problem is just government issues, therefore waste problem become hard to be solve. This researched has been conducted in primary school and junior high school. The research purpose are to find out how deep of student knowlege about waste and waste management, also to find out what impact that happen with student after 3R programs was conducted. The methodology of this research is colecting primary and secondary data, do interview, run the game about 3R and do anlysis data. From analysis data can conclude that there ist incresing value of knowledge and attitude about environment awareness and waste management arround 18 – 25%.